Robust approach for efficiency measurement of employee performance under profit sharing system - Mahmudah, Umi; Lola, Muhamad Safiih (Economic Journal of Emerging Markets, 2018)
This study estimates the efficiency of employees’ performances under profit sharing system using data envelopment analysis (DEA). This method is one of the most common methods used in efficiency measurement analysis. However, a robust approach is used to deal with the complexity of the traditional DEA estimators. Robust Data Envelopment Analysis (RDEA) is very useful when outliers contaminate the data. The sample includes five divisions which cover as many as 102 employees of a shipping company in Malaysia are analyzed by using R program. The results reveal that the initial DEA efficiency is an over-estimate of the true efficiency. RDEA provides better accuracy of the results. Further, the robust approach is appropriate to be used in the measurement of the efficiency of company divisions under profit sharing program.